2016
DOI: 10.1177/1475240916659722
|View full text |Cite
|
Sign up to set email alerts
|

Structures and programme supports for Creativity, Action, Service in the International Baccalaureate Diploma Programme: An implementation study in Turkey

Abstract: This qualitative multiple-case study examined the implementation of an experiential learning component of an academic curriculum in six high schools in Turkey. Structures and supports that influenced programme implementation were examined using an implementation framework adapted from Durlak and Dupre. The study describes how the experiential learning programme is implemented. Findings indicate four areas that need ongoing attention: (1) supports for programme coordinators, (2) teacher training, (3) integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…This would be a productive line for future research since it is plausible that adopting the aims and approaches of the IB may be difficult for teachers from countries where student-centred teaching is not common. For example, some DP teachers in a study conducted by Martin, Tanyu and Perry (2016) in Turkey reported that they struggled with the IB’s student-centered instructional approach because it differs from the teacher-centered, didactic approach that is commonly used in their country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be a productive line for future research since it is plausible that adopting the aims and approaches of the IB may be difficult for teachers from countries where student-centred teaching is not common. For example, some DP teachers in a study conducted by Martin, Tanyu and Perry (2016) in Turkey reported that they struggled with the IB’s student-centered instructional approach because it differs from the teacher-centered, didactic approach that is commonly used in their country.…”
Section: Resultsmentioning
confidence: 99%
“…Other challenges related to curriculum have been uncovered, all relating to the DP. These are the time teachers require to plan, prepare and deliver the DP (Doherty & Shield, 2012); difficulties in balancing the demands of the DP with national curriculum (Martin et al, 2016); and difficulty balancing the academic demands of the DP with its experiential learning component (Martin et al, 2016). Some teachers in Hong Kong reported that they did not always agree with the values embedded in the DP, which they felt was western-biased (Lai et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Existing research suggests that experiential learning arising from participating in CAS has the potential to be transformative (Hayden and McIntosh, 2018), increasing students' awareness of socio-economic issues and their own role in promoting social change (Lindemann, 2012). The way in which CAS is implemented (Kulundu and Hayden, 2002) and how CAS is valued in individual schools (Martin et al, 2016) is mediated by CAS Coordinators and IB Diploma Coordinators in particular. Coordinators tend to have leadership roles that involve contact with parents.…”
Section: Communities Of Educational Practicementioning
confidence: 99%
“…Although the Coordinator perceives parents prioritising academic work in this school in the Middle East, it is also clear that the institutional constraints on time and space for CAS tacitly reinforce messages that value it less than academic subjects. Similarly, research in Turkish schools suggests that a CAS programme complementing schools' values is more likely to engage students and meet programme aims than a programme in a school where the IB Diploma is seen only as a passport to university (Martin et al, 2016). Thus, CAS and academic subjects relate to different goals and values.…”
Section: Knowledge Hierarchymentioning
confidence: 99%
“…Además, algunos trabajos empíricos presentan una ausencia de datos, tales como el tamaño global de la muestra (e.g. Brodie, 2014;Martin et al, 2016) o la diferenciación del tamaño muestral por países (e.g. Brodie, 2014).…”
Section: Limitacionesunclassified